2014
DOI: 10.1111/tbed.12276
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Porcine Circovirus 2 Associated Reproductive Failure in Southern India

Abstract: Incidence of unusually high numbers of stillbirths was observed at a piggery unit at the Veterinary University research farm in Tamil Nadu State of India. Systematic examination of the tissue from stillborn piglets led to the identification of presence of Porcine circovirus 2 (PCV2). Detailed analysis utilizing electron microscopy, polymerase chain reaction and sequencing confirmed the presence of PCV2 in the tissue of affected piglets. Histopathology analysis of the affected piglet tissue showed lymphoid cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…No vaccination against PCV2 was done in study areas reported in the present manuscript. It has been reported that PCV2 infections are associated with stillbirths and reproductive failure (Karuppannan et al., ). Due to unrestricted movement of animals and their products, transboundary diseases of pigs such as PRRSV and PCV are spreading to the NER of India.…”
Section: Discussionmentioning
confidence: 99%
“…No vaccination against PCV2 was done in study areas reported in the present manuscript. It has been reported that PCV2 infections are associated with stillbirths and reproductive failure (Karuppannan et al., ). Due to unrestricted movement of animals and their products, transboundary diseases of pigs such as PRRSV and PCV are spreading to the NER of India.…”
Section: Discussionmentioning
confidence: 99%
“…The fetal pathogen PCV2 was first reported by Karuppannan et al (2016), who found that PCV2 transplacental infection resulted in viral infection of embryos or fetuses in sows. Sarli et al (2012) found that reproductive failure could be experimentally induced in sows via artificial insemination with PCV2b-spiked semen.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, the PMWS and other porcine circovirus associated diseases (PCVAD) have caused severe economic losses to the global swine industry. One such disease, porcine-circovirus-associated reproductive failure, has been diagnosed on numerous PCV2-contaminated swine farms (de Castro et al 2012, Karuppannan et al 2016. Stillbirths, mummification, embryonic death, dysgenesis, declines in spermatozoa quality and decreases in litter size were common findings in the field of PCV2-associated reproCorrespondence to: Z.B.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them PCV2a and PCV2b are the most prevalent genotypes in the pig raising farms worldwide [8,9]. In the past less than one decade, more genetic variations and recombination associated with PCV2 have been reported worldwide [10][11][12][13][14][15][16][17][18][19][20]. It is important that a 1766 nt PCV2 strain (YJ) with ORF2 of 708 nt has been first isolated from the clinically infected pig with PCVAD in china.…”
Section: Q2mentioning
confidence: 99%